What Factors Influence a Firm Value? Optimistic Financial Performance - Harnovinsah Harnovinsah; Ana Sopanah; Yayan Hadijah; Hanif Rani Iswari; Iva Khoiril Mala; lina saptaria (JMK (Jurnal Manajemen dan Kewirausahaan), 2023)
Company value is formed in various performance factors. In this study the capital structure, profitability, size and type of company are investigated in its role in building company value. The company that is the object of research is a food and beverage consumer goods company listed on the Indonesia Stock Exchange in 2015-2019. This research is a quantitative research. The research sample was 13 subsectors of food and beverage consumption goods listed on the Indonesia Stock Exchange. Regent analysis is used in gathering panel data in this study. There are several diverse research results, namely partially capital structure (DER), profitability (ROA) has a positive significant effect on company value (PBV). While the company's size has a negative effect on the company value (PBV) and company growth has no effect on the company's value (PBV). The implications of this study provide contributing to further research and are able to provide knowledge to company decision making related to efforts to increase company value.Keywords: firm size, price to book value, debt-equity ratio, return on assets, company growth,